Peran KSOP dalam Menertibkan Tenaga Kerja Bongkar Muat melalui Simon TKBM di Pelabuhan Belawan - Manalu, Afrendi; Faris Novandi; Diana Alia; Muhammad Dahri (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Belawan Port as the main port in Indonesia plays an important role in international trade. The Main Harbormaster and Port Authority Office (KSOP) of Belawan has the authority to supervise operational activities at the Port including regulating stevedoring workers (TKBM). This regulation is implemented through the TKBM Monitoring System (SIMON TKBM) to manage workers efficiently, transparently, and safely. This study uses a qualitative descriptive approach with literature study methods, interviews, observations and documentation then analyzed using data reduction methods, data presentation and drawing conclusions. The results of the study showed that the role of KSOP is very central in regulating TKBM through SIMON TKBM which includes TKBM supervision, competency improvement, rule enforcement, and coordination with stakeholders. However, technical obstacles were also found including the failure of duplicate data management and the absence of an automatic age filter in the system, as well as practical obstacles, namely the lack of coordination regarding TKBM competency certificates.